Role of epicardial adipose tissue in the pathogenesis of chronic inflammation in heart failure with preserved ejection fraction - O. N. Dzhioeva; Yu. S. Timofeev; V. A. Metelskaya; A. A. Bogdanova; T. Yu. Vedenikin; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2024)
According to the recent World Health Organization statistics, cardiovascular disease (CVD) is one of the leading causes of high mortality worldwide. While obesity is a major and persistent risk factor for CVD, the cause of this condition, the pathological molecular connection between peripheral fat depots and the heart, remains poorly understood. The aim of this review is to introduce the reader to the metabolic activity of epicardial adipose tissue (EAT), the consequences of excessive epicardial fat accumulation and the development of heart failure (HF).EAT is visceral adipose tissue that is in direct contact with the myocardium and coronary vessels and can influence cardiac function through both mechanical effects and more subtle paracrine molecular mechanisms. HF with preserved ejection fraction (HFpEF) is closely associated with obesity and patterns in fat distribution. Excessive amounts of EAT are associated with abnormal hemodynamics in HFpEF, with the potential for direct mechanical effects on the heart causing a constriction-like effect and local myocardial remodeling effects resulting from the secretion of inflammatory mediators. However, patients with excess EAT tend to have more subcutaneous adipose tissue, making it difficult to determine a cause-and-effect relationship between epicardial fat and HFpEF. This review provides evidence that excess EAT is an important part of HFpEF pathogenesis.